The Utilization of Email and WhatsApp among Muhammadiyah Regional Leaders in Medan City - Winda Kustiawan; Syukur Kholil; Yusnadi Yusnadi (Budapest International Research and Critics University, 2019)
The aim of this research is to describe the utilization of email and whatsapp among Muhammadiyah Regional Leaders in Medan City. This research uses descriptive qualitative approach. The results show that the use of email and whatsapp among Muhammadiyah Regional Leaders in Medan City that they understand the reasons for using email and whatsapp as a means of organizational information, the considerations are Trend, Application, Features, Fast and Capacity. Media other than email and whatsapp, they use Facebook, Twitter, Line, Instagram and Messenger. Effects of whatsapp Utilization Used because of its speed, its distribution are easy and can be done selectively. Next the categorization of the utilization of whatsapp used by Muhammadiyah Leaders of Medan City that fast access, low cost, features, more effective and faster information delivered so that it becomes a strategic customer. The advantages of using whatsapp are more trends, easy coordination, more convenience and easier and cheaper. So from this it facilitates organizational activities, connecting quickly with other leaders and mastering the media as a source of effective information and communication within the organization. The messages which is obtained by the Muhammadiyah Regional Head of Medan City from email and whatsapp is that the Leaders can understand the characteristics of Email usage and whatsapp.